↑ Top


Homomorphism Theorems

This is the Base.Homomorphisms.Noether module of the Agda Universal Algebra Library.

{-# OPTIONS --without-K --exact-split --safe #-}

open import Overture using ( 𝓞 ; 𝓥 ; Signature )

module Base.Homomorphisms.Noether {𝑆 : Signature 𝓞 𝓥} where

-- Imports from Agda and the Agda Standard Library ---------------------------------------
open  import Data.Product     using ( Σ-syntax ; _,_ ; _×_ )
                              renaming ( proj₁ to fst ; proj₂ to snd )
open  import Function         using ( _∘_ ; id )
open  import Level            using (Level )
open  import Relation.Binary  using ( IsEquivalence )

open  import Relation.Binary.PropositionalEquality as ≡
      using ( module ≡-Reasoning ; _≡_ )

-- Imports from agda-algebras --------------------------------------------------------------
open import Base.Relations         using ( ⌞_⌟ ; mkblk ; ⟪_⟫ )
open import Overture               using ( ∣_∣ ; ∥_∥ ; _⁻¹ )
open import Base.Functions         using ( Image_∋_ ; IsInjective ; SurjInv )
                                   using ( IsSurjective ; SurjInvIsInverseʳ )

open import Base.Algebras {𝑆 = 𝑆}  using ( Algebra ; _̂_ ; Con ; IsCongruence )

open  import Base.Homomorphisms.Kernels {𝑆 = 𝑆}
      using ( kercon ; ker[_⇒_]_↾_ ; πker )

open  import Base.Equality
      using ( swelldef ; is-set ; blk-uip ; is-embedding ; monic-is-embedding|Set )
      using ( pred-ext ; block-ext|uip )

open  import Base.Homomorphisms.Basic {𝑆 = 𝑆}
      using ( hom ; is-homomorphism ; epi ; epi→hom )

private variable α β γ : Level

The First Homomorphism Theorem

Here we formalize a version of the first homomorphism theorem, sometimes called Noether’s first homomorphism theorem, after Emmy Noether who was among the first proponents of the abstract approach to the subject that we now call “modern algebra”).

Informally, the theorem states that every homomorphism from 𝑨 to 𝑩 (𝑆-algebras) factors through the quotient algebra 𝑨 ╱ ker h (𝑨 modulo the kernel of the given homomorphism). In other terms, given h : hom 𝑨 𝑩 there exists φ : hom (𝑨 ╱ ker h) 𝑩 which, when composed with the canonical projection πker : 𝑨 ↠ 𝑨 ╱ ker h, is equal to h; that is, h = φ ∘ πker. Moreover, φ is a monomorphism (injective homomorphism) and is unique.

Our formal proof of this theorem will require function extensionality, proposition extensionality, and a couple of truncation assumptions. The extensionality assumptions are postulated using swelldef and pred-ext which were defined in Base.Equality.Welldefined and Base.Equality.Extensionality. As for truncation, to prove that φ is injective we require

To prove that φ is an embedding we require

Note that the classical, informal statement of the first homomorphism theorem does not demand that φ be an embedding (in our sense of having subsingleton fibers), and if we left this out of the consequent of our formal theorem statement, then we could omit from the antecedent the assumption that ∣ 𝑩 ∣ is a set.

Without further ado, we present our formalization of the first homomorphism theorem.

open ≡-Reasoning

FirstHomTheorem|Set : (𝑨 : Algebra α 𝑆)(𝑩 : Algebra β 𝑆)(h : hom 𝑨 𝑩)
 {- extensionality assumptions -}  (pe : pred-ext α β)(fe : swelldef 𝓥 β)
 {- truncation assumptions -}      (Bset : is-set ∣ 𝑩 ∣)
                                   (buip : blk-uip ∣ 𝑨 ∣ ∣ kercon fe {𝑩} h ∣)
     -------------------------------------------------------------------------
 →   Σ[ φ ∈ hom (ker[ 𝑨 ⇒ 𝑩 ] h ↾ fe) 𝑩  ]
     ( ∣ h ∣ ≡ ∣ φ ∣ ∘ ∣ πker fe{𝑩}h ∣ × IsInjective ∣ φ ∣  ×  is-embedding ∣ φ ∣  )

FirstHomTheorem|Set 𝑨 𝑩 h pe fe Bset buip = (φ , φhom) , ≡.refl , φmon , φemb
 where
  θ : Con 𝑨
  θ = kercon fe{𝑩} h
  ξ : IsEquivalence ∣ θ ∣
  ξ = IsCongruence.is-equivalence ∥ θ ∥

  φ : ∣ (ker[ 𝑨 ⇒ 𝑩 ] h ↾ fe) ∣ → ∣ 𝑩 ∣
  φ a = ∣ h ∣ ⌞ a ⌟

  φhom : is-homomorphism (ker[ 𝑨 ⇒ 𝑩 ] h ↾ fe) 𝑩 φ
  φhom 𝑓 a =  ∣ h ∣ ( (𝑓 ̂ 𝑨) (λ x → ⌞ a x ⌟) )  ≡⟨ ∥ h ∥ 𝑓 (λ x → ⌞ a x ⌟)  ⟩
              (𝑓 ̂ 𝑩) (∣ h ∣ ∘ (λ x → ⌞ a x ⌟))  ≡⟨ ≡.cong (𝑓 ̂ 𝑩) ≡.refl     ⟩
              (𝑓 ̂ 𝑩) (λ x → φ (a x))            ∎

  φmon : IsInjective φ
  φmon {_ , mkblk u ≡.refl} {_ , mkblk v ≡.refl} φuv = block-ext|uip pe buip ξ φuv

  φemb : is-embedding φ
  φemb = monic-is-embedding|Set φ Bset φmon

Below we will prove that the homomorphism φ, whose existence we just proved, is unique (see NoetherHomUnique), but first we show that if we add to the hypotheses of the first homomorphism theorem the assumption that h is surjective, then we obtain the so-called first isomorphism theorem. Naturally, we let FirstHomTheorem|Set do most of the work.

FirstIsoTheorem|Set : (𝑨 : Algebra α 𝑆) (𝑩 : Algebra β 𝑆) (h : hom 𝑨 𝑩)
 {- extensionality assumptions -}  (pe : pred-ext α β) (fe : swelldef 𝓥 β)
 {- truncation assumptions -}      (Bset : is-set ∣ 𝑩 ∣)
                                   (buip : blk-uip ∣ 𝑨 ∣ ∣ kercon fe{𝑩}h ∣)
 →                                 IsSurjective ∣ h ∣
 →                                 Σ[ f ∈ (epi (ker[ 𝑨 ⇒ 𝑩 ] h ↾ fe) 𝑩)]
                                   ( ∣ h ∣ ≡ ∣ f ∣ ∘ ∣ πker fe{𝑩}h ∣  × IsInjective ∣ f ∣ × is-embedding ∣ f ∣ )

FirstIsoTheorem|Set 𝑨 𝑩 h pe fe Bset buip hE =
 (fmap , fhom , fepic) , ≡.refl , (snd ∥ FHT ∥)
  where
  FHT = FirstHomTheorem|Set 𝑨 𝑩 h pe fe Bset buip

  fmap : ∣ ker[ 𝑨 ⇒ 𝑩 ] h ↾ fe ∣ → ∣ 𝑩 ∣
  fmap = fst ∣ FHT ∣

  fhom : is-homomorphism (ker[ 𝑨 ⇒ 𝑩 ] h ↾ fe) 𝑩 fmap
  fhom = snd ∣ FHT ∣

  fepic : IsSurjective fmap
  fepic b = Goal where
   a : ∣ 𝑨 ∣
   a = SurjInv ∣ h ∣ hE b

   bfa : b ≡ fmap ⟪ a ⟫
   bfa = ((SurjInvIsInverseʳ ∣ h ∣ hE) b)⁻¹

   Goal : Image fmap ∋ b
   Goal = Image_∋_.eq ⟪ a ⟫ bfa

Now we prove that the homomorphism φ, whose existence is guaranteed by FirstHomTheorem|Set, is unique.

module _ {fe : swelldef 𝓥 β}(𝑨 : Algebra α 𝑆)(𝑩 : Algebra β 𝑆)(h : hom 𝑨 𝑩) where

 FirstHomUnique :  (f g : hom (ker[ 𝑨 ⇒ 𝑩 ] h ↾ fe) 𝑩)
  →                ∣ h ∣ ≡ ∣ f ∣ ∘ ∣ πker fe{𝑩}h ∣
  →                ∣ h ∣ ≡ ∣ g ∣ ∘ ∣ πker fe{𝑩}h ∣
  →                ∀ a  →  ∣ f ∣ a ≡ ∣ g ∣ a

 FirstHomUnique f g hfk hgk (_ , mkblk a ≡.refl) =
  ∣ f ∣ (_ , mkblk a ≡.refl)  ≡⟨ ≡.cong-app(hfk ⁻¹)a ⟩
  ∣ h ∣ a                     ≡⟨ ≡.cong-app(hgk)a ⟩
  ∣ g ∣ (_ , mkblk a ≡.refl)  ∎

If, in addition, we postulate extensionality of functions defined on the domain ker[ 𝑨 ⇒ 𝑩 ] h, then we obtain the following variation of the last result. (See Base.Equality.Truncation for a discussion of truncation, sets, and uniqueness of identity proofs.)

fe-FirstHomUnique :  {fuww : funext (α ⊔ lsuc β) β}(f g : hom (ker[ 𝑨 ⇒ 𝑩 ] h ↾ fe) 𝑩)
  →                  ∣ h ∣ ≡ ∣ f ∣ ∘ ∣ πker fe{𝑩}h ∣
  →                  ∣ h ∣ ≡ ∣ g ∣ ∘ ∣ πker fe{𝑩}h ∣
  →                  ∣ f ∣ ≡ ∣ g ∣

 fe-FirstHomUnique {fuww} f g hfk hgk = fuww (NoetherHomUnique f g hfk hgk)

The proof of NoetherHomUnique goes through for the special case of epimorphisms, as we now verify.

 FirstIsoUnique :  (f g : epi (ker[ 𝑨 ⇒ 𝑩 ] h ↾ fe) 𝑩)
  →                ∣ h ∣ ≡ ∣ f ∣ ∘ ∣ πker fe{𝑩}h ∣
  →                ∣ h ∣ ≡ ∣ g ∣ ∘ ∣ πker fe{𝑩}h ∣
  →                ∀ a → ∣ f ∣ a ≡ ∣ g ∣ a

 FirstIsoUnique f g hfk hgk = FirstHomUnique (epi→hom 𝑩 f) (epi→hom 𝑩 g) hfk hgk

← Base.Homomorphisms.Products Base.Homomorphisms.Factor →